Impact of coronavirus disease 2019 on urgent referrals to secondary care otolaryngology: a prospective case series. Issue 11 (28th November 2020) - Osborne, M S; Bentley, E; Farrow, A; Chan, J; Murphy, J
Abstract: Objective: As the novel coronavirus disease 2019 changed patient presentation, this study aimed to prospectively identify these changes in a single ENT centre. Design: A seven-week prospective case series was conducted of urgently referred patients from primary care and accident and emergency department. Results: There was a total of 133 referrals. Referral rates fell by 93 per cent over seven weeks, from a mean of 5.4 to 0.4 per day. Reductions were seen in referrals from both primary care (89 per cent) and the accident and emergency department (93 per cent). Presentations of otitis externa and epistaxis fell by 83 per cent, and presentations of glandular fever, tonsillitis and peritonsillar abscess fell by 67 per cent. Conclusion: Coronavirus disease 2019 has greatly reduced the number of referrals into secondary care ENT. The cause for this reduction is likely to be due to patients' increased perceived risk of the virus presence in a medical setting. The impact of this reduction is yet to be ascertained, but will likely result in a substantial increase in emergency pressures once the lockdown is lifted and the general public's perception of the coronavirus disease 2019 risk reduces.